2017
DOI: 10.1111/tbed.12791
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of widespread foot‐and‐mouth disease virus serotypes A, O and Asia‐1 in southern Asia: A Bayesian phylogenetic perspective

Abstract: Foot-and-mouth disease (FMD) is, arguably, the animal disease with the most devastating global economic impact owing in part, to the severe trade restrictions imposed upon affected countries and regions. South Asia is one of the regions where widespread lineages of the FMDV virus (FMDV) have emerged. Here, we performed an integrative phylogenetic analysis of all FMDV serotypes (A, O and Asia-1) circulating in southern Asia, including viral sequences collected until 2013. Our results describe the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Based on estimated VP1 nucleotide substitution rates obtained by Bayesian divergence‐time estimation methods, the number of expected nucleotide changes in VP1 per year has been reported as 3.75 (3.06–4.43; corresponding to 5.92 × 10 −3 substitutions/site/year) for lineage O/PanAsia2, 2.46 (1.76–3.17; 3.88 × 10 −3 substitutions/site/year) for Asia‐1/Sindh08, and 10.95 (8.99–13.10; 1.73 × 10 −2 substitutions/site/year) for A/Iran‐05 (Brito et al., ). Previous studies have reported similar nucleotide substitution rates for O/PanAsia2 and A/Iran‐05 based on linear regression analysis of genetic distances (Jamal, Ferrari, Ahmed, Normann, & Belsham, 2011a; Jamal, Ferrari, Ahmed, Normann, Curry et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on estimated VP1 nucleotide substitution rates obtained by Bayesian divergence‐time estimation methods, the number of expected nucleotide changes in VP1 per year has been reported as 3.75 (3.06–4.43; corresponding to 5.92 × 10 −3 substitutions/site/year) for lineage O/PanAsia2, 2.46 (1.76–3.17; 3.88 × 10 −3 substitutions/site/year) for Asia‐1/Sindh08, and 10.95 (8.99–13.10; 1.73 × 10 −2 substitutions/site/year) for A/Iran‐05 (Brito et al., ). Previous studies have reported similar nucleotide substitution rates for O/PanAsia2 and A/Iran‐05 based on linear regression analysis of genetic distances (Jamal, Ferrari, Ahmed, Normann, & Belsham, 2011a; Jamal, Ferrari, Ahmed, Normann, Curry et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Sequence analysis of the FMDV VP1‐coding region has suggested that complex mixtures of genotypes may arise during FMDV type O persistent infection in Asian buffalo, providing a potential source of novel viral variants (Barros, Malirat, Rebello, Costa, & Bergmann, ). Likewise, rapid viral evolution has been described during FMDV persistent infection of cattle (Brito et al., ; Gebauer et al., ). However, a different investigation suggested more limited changes within the viral genome during persistent infection in cattle (Parthiban et al., ).…”
Section: Introductionmentioning
confidence: 94%
“…We investigated and compared the historical spreads of FMDV at serotype level, from the ones with local distribution (Asia1 and SATs) to the serotypes with widespread dispersal (O and A) [26,28,34,55,77,78].…”
Section: Spatiotemporal Diffusion Among Serotypesmentioning
confidence: 99%
“…FMDV causes the most influential transboundary animal disease with historical worldwide circulation reported in domestic and wildlife reservoirs [25,26]. FMD is a highly contagious disease caused by a small single-stranded RNA virus of the genus Aphthovirus, member of the family Picornaviridae [27] and classified into seven different serotypes; O, A, C, Asia1 and Southern African Territories (SATs) 1, 2 and 3 [25,[28][29][30] which severely affect the productivity of domesticated livestock, causing great economic losses [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation